Bullying Victimization Prevalence and Its Effects on Psychosomatic Complaints: Can Sense of Coherence Make a Difference?. (October 2014) - García‐Moya, Irene; Suominen, Sakari; Moreno, Carmen
ABSTRACT BACKGROUND The aim of this study was to examine the prevalence of bullying victimization and its impact on physical and psychological complaints in a representative sample of adolescents and to explore the role of sense of coherence (SOC) in victimization prevalence and consequences. METHODS A representative sample of Spanish adolescents (N = 7580, mean age = 15.41) was selected as part of the Health Behaviour in School‐aged Children study. Bullying victimization, physical and psychological symptoms, and SOC were measured, and comparisons were made between strong‐ and weak‐SOC adolescents regarding their likelihood of being a victim of bullying and the negative effects of bullying victimization on their health. RESULTS Weak‐SOC adolescents were significantly more likely to suffer from bullying victimization regardless of type (nonphysical vs physical and nonphysical) or means (traditional vs cyberbullying). In addition, bullying victimization showed significant increasing effects on weak‐SOC adolescents' physical and psychological symptoms whereas in strong‐SOC adolescents it was not significantly associated with increases in physical complaints and its effects on psychological complaints seemed to be weaker. CONCLUSIONS Weak‐SOC adolescents seem to be at higher risk of becoming bullying victims and victimization experiences appear to have increased negative effects on them when compared to strong‐SOC students.